2002
DOI: 10.1203/00006450-200203000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Direct Measurement of Intratracheal Pressure in Pediatric Respiratory Monitoring

Abstract: We describe a method based on a Fabry-Perot interferometer at the tip of an optic fiber with a diameter of 0.25 mm for direct measurement of tracheal pressure in pediatric respiratory monitoring. The response time of the pressure transducer and its influence on the resistance of pediatric endotracheal tubes (internal diameter, 2.5 to 5 mm) during constant and dynamic flow at different ventilator settings in a lung model were measured. The transducer was positioned at Ϫ1.5 (inside), 0, and ϩ1.5 cm (outside) rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 12 publications
3
41
0
1
Order By: Relevance
“…In contrast, mean airway pressure was significantly greater in the IMV group (z 13 cm H 2 O) for the same level of Pa CO 2 . Though we did not measure intratracheal pressures during the application of IMV, a prior study has shown that, with a cuffed endotracheal tube in place, intratracheal measured pressures closely approximate the ventilator-delivered pressures (36). Tracheal gas insufflation has been shown to adequately support ventilation and oxygenation at low airway pressures in neonates with respiratory disease and other pathologic settings (37).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, mean airway pressure was significantly greater in the IMV group (z 13 cm H 2 O) for the same level of Pa CO 2 . Though we did not measure intratracheal pressures during the application of IMV, a prior study has shown that, with a cuffed endotracheal tube in place, intratracheal measured pressures closely approximate the ventilator-delivered pressures (36). Tracheal gas insufflation has been shown to adequately support ventilation and oxygenation at low airway pressures in neonates with respiratory disease and other pathologic settings (37).…”
Section: Discussionmentioning
confidence: 96%
“…It consists of a membrane that changes the depth of a microcavity with pressure (Fabry-Perot interferometry). It shows some advantages such as: small size (the silicon sensor chip diameter is equal to 420 µm, the fiber optic diameter is 250 µm or 400 µm), measurement range between -50 cmH 2 O and +350 cmH 2 O, low temperature drift (< 0.2 cmH 2 O/°C), accuracy of 0.5 cmH 2 O or 2.5 % of reading between -50 cmH 2 O to +250 cmH 2 O and 4 % of reading between +250 cmH 2 O to +350 cmH 2 O, short response time (1.3 ms), moreover the introduction of the sensor into the ETT does not significantly increase the fluid-dynamic resistance, therefore the pressure drop across the ETT (Sondergaard et al, 2002). This company produces another FOS, with similar metrological characteristics of the above described sensor, used in urology to monitor bladder pressure and the pressure in the lower urinary tract, especially important in paraplegic patients for the high risk of urinary tract infections.…”
Section: Interferometry-based and Intensity-modulated Fiber Optic Senmentioning
confidence: 99%
“…The details of the Samba sensor (Sensor 1) were presented previously (Sondergaard et al, 2002). Because this sensor is designed for use in fluids and gases, we connected it to a small water-filled rubber balloon, which was positioned between the calf muscles ( Fig.…”
Section: Pressure Measurementsmentioning
confidence: 99%
“…Whereas the microcapillary infusion technique was used in earlier investigations on IaMP determination (Styf and Körner, 1986), transducer-tipped semiconductor-based or fibre-optic-based catheter pressure sensors were used in more recent studies (Sondergaard et al, 2002;Kaufman et al, 2003;Cottler et al, 2009;Sezen et al, 2009). Because these methods require a fluid-filled space, which is nonexistent between muscles, they are not suitable to measure the IrMP.…”
Section: Introductionmentioning
confidence: 99%